Sex Work, Sex Workers and Forms of Inequality: A Policy Brief - Tsertekidis, Georgios (HAPSc Policy Briefs Series, 2023)
Sex work has always been here. It has many types and expressions. According to existing scholarship, sex work is associated with a variety of inequalities. Evidence from academic literature shows that, worldwide, sex workers face serious inequalities with severe effects on their lives. Through this policy brief, inequalities are classified by context in some main categories. Social, economic, racial/ethnic, gender, age and “beauty” as well as health inequalities, as demonstrated by international literature, plague sex workers at a global scale. Taking all the above into account, conclusions are drawn and possible solutions are recommended for the mitigation and -if possible- elimination of these inequalities, utilizing means at a local, national and international scale.